1997
DOI: 10.1111/j.1460-9568.1997.tb01489.x
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Metabotropic Glutamate (mGlu) Receptors Tonically Inhibit Transmitter Release in Rat Caudate Nucleus: In Vivo Studies with (2S,1′S,2′S,3′R)‐2‐(2′‐carboxy‐3′‐phenylcyclopropyl)glycine, a New Potent and Selective Antagonist

Abstract: Anatomical, biochemical and electrophysiological studies have previously shown that cortico-striatal terminals contain abundant presynaptic group 2 metabotropic glutamate (mGlu) receptors. Using brain slices we have previously shown that these receptors inhibit depolarization-induced transmitter release. Using microdialysis in freely moving rats, we now report the effects of group 2 mGlu receptor agonists and antagonists on glutamate concentration in the caudate extracellular fluid. A mild decrease (20-30%) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 29 publications
1
34
1
Order By: Relevance
“…Speci®-cally, we found that, compared with vehicle, pretreatment with 100 or 400 nmol (2R,4R)-APDC, and 25 or 100 nmol L-AP4 signi®cantly reduced the amount of time rats spent exhibiting SNBs. We believe the observed anti-nociceptive effects of the group II or group III mGluR agonists are attributable to their well established ability to decrease glutamate release in various CNS structures [11,12]. In support of this, group II and III mGluR agonists have been found to reduce synaptic excitation in models associated with enhanced glutamate release.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Speci®-cally, we found that, compared with vehicle, pretreatment with 100 or 400 nmol (2R,4R)-APDC, and 25 or 100 nmol L-AP4 signi®cantly reduced the amount of time rats spent exhibiting SNBs. We believe the observed anti-nociceptive effects of the group II or group III mGluR agonists are attributable to their well established ability to decrease glutamate release in various CNS structures [11,12]. In support of this, group II and III mGluR agonists have been found to reduce synaptic excitation in models associated with enhanced glutamate release.…”
Section: Discussionmentioning
confidence: 67%
“…Thus, it is expected that the nociceptive effects of spinal (RS)-DHPG may depend, at least partly, on an enhanced release of glutamate in the spinal cord dorsal horn. In contrast, activation of the group II (mGluR2 and mGluR3) and group III (mGluR4, mGluR6±8) mGluRs has been shown to decrease EAA release in the CNS [11,12]. Thus, it is possible group II and III mGluRs may be effective at alleviating persistent nociception by inhibiting glutamate release in the spinal cord dorsal horn.…”
Section: Introductionmentioning
confidence: 82%
“…It should be noted that ACPD in the presently used concentration did not significantly increase basal DA release in the NAcc, in contrast to higher concentrations (Ohno and Watanabe, 1995;. It is not known whether a relation exists between the inhibitory actions of ACPD and the inhibition of striatal glutamate release, which was described recently for this drug (Lombardi et al, 1994;Cozzi et al, 1997), or whether these release-inhibiting actions extend to DA terminals in this brain area.…”
Section: Figmentioning
confidence: 87%
“…One hypothetical advantage associated with the use of mGlu receptor ligands is the lack of the adverse effects typically induced by NMDA or AMPA receptor antagonists, such as sedation, ataxia, and severe learning impairment Bruno et al, 2001). Of the eight known mGlu receptor subtypes, mGlu2 and mGlu3 receptors are the best candidates as "neuroprotective receptors," because their activation inhibits glutamate release (Lovinger, 1991;Lovinger and McCool, 1995;Battaglia et al, 1997;Cozzi et al, 1997), inhibits voltage-gated calcium channels (for review, see Pin and Duvoisin, 1995), positively modulates potassium channels (Sharon et al, 1997), and stimulates the production of neurotrophic factors in astrocytes and microglia (Bruno et al, 1997(Bruno et al, , 1998bCiccarelli et al, 1999;D'Onofrio et al, 2001;Matarredona et al, 2001). Early in vitro studies have shown that first generation agonists of mGlu2 and mGlu3, such as (2S,1ЈS,2ЈS)-2-(carboxycyclopropyl)glycine and (2S,2ЈR,3ЈR)-2-(2Ј,3Ј-dicarboxycyclopropyl)glycine, are protective against excitotoxicity and other neuronal insults (Pizzi et al, 1993;Bruno et al, 1994Bruno et al, , 1995Ambrosini et al, 1995;Buisson and Choi, 1995;Thomsen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%